Signification du lieu d’origine des colons en Nouvelle-France - Charbonneau, Hubert (Mémoires de la Société généalogique canadienne-française, 1993)
Keywords: Français

The Common Ground. Settled Natives and French in Montréal 1667-1760 - Grabowski, Jan (Université de Montréal, 1993)
Amérindiens ; Français ; Régime français
Keywords: Autochtones; Français

La Nouvelle-France sous Joseph-Antoine Le Febvre de La Barre, 1682-1685: lettres, mémoires, instructions et ordonnances - Dubé, Pauline (Septentrion, 1993)
Keywords: Autochtones; Français; Gouverneurs

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Les filles du roi et les soldats du régiment de Carignan-Salières - Landry, Yves (Cap-aux-Diamants, 1993)
Keywords: Armée; Filles du Roi; Français

La vie musicale à Montréal sous le régime français - Gallat-Morin, Élisabeth (Les origines de Montréal. Actes du colloque organisé par la Société historique de Montréal, 1993)
Keywords: Musicien; Musique

Jean Girard: musicien en Nouvelle-France: Bourges, 1696 - Montréal, 1765 - Gallat-Morin, Élisabeth (Septentrion, 1993)
Keywords: Girard, Jean; Musicien; Musique

Le clergé en Nouvelle-France: étude démographique et répertoire biographique - Pelletier, Louis (Presses de l'Université de Montréal, 1993)

«C'est l'eau-de-vie qui a commis ce meurtre». Alcool et criminalité amérindienne à Montréal sous le Régime français - Dickinson, John A. (Études canadiennes / Canadian Studies, 1993)
Keywords: Alcool; Autochtones; Criminalité

Les dits et gestes des "Véritables motifs de messieurs et dames de la Société de Notre-Dame de Montréal, pour la conversion des sauvages de Nouvelle-France" - Bazinet, Louis (Les origines de Montréal. Actes du colloque organisé par la Société historique de Montréal, 1993)
Keywords: Société de Notre-Dame de Montréal